2021
DOI: 10.1177/20499361211034070
|View full text |Cite
|
Sign up to set email alerts
|

Non-recommended medical interventions and their possible harm in patients with COVID-19

Abstract: The disease caused by the SARS-CoV-2 virus (COVID-19) can manifest itself through more than 80 symptoms and signs, considering it a multisystemic disease. 1 However, the disease is classified according to the pulmonary involvement evaluated through the measurement of the respiratory rate, respiratory signs and symptoms, oxygen saturation (SatO 2 ), the ratio of arterial oxygen pressure to inspired oxygen fraction (PaO 2 /FiO 2 ), and the extent of lung lesions seen on non-contrast chest tomography. The leading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…With a lack of therapies acting directly against SARS-CoV-2, patients in our cohort were treated with remdesivir and hydroxychloroquine according to Dutch guidelines at that time before evidence of a beneficial effect. Treatment with hydroxychloroquine got remarkable attention primarily due to in vitro data and immunomodulatory capacities, but a meta-analysis demonstrated an association with increased mortality and no clear benefit in hospitalized COVID-19 patients [ 34 , 35 ]. In different clinical trials, treatment with remdesivir showed mixed results and seemed to shorten time to recovery [36] .…”
Section: Discussionmentioning
confidence: 99%
“…With a lack of therapies acting directly against SARS-CoV-2, patients in our cohort were treated with remdesivir and hydroxychloroquine according to Dutch guidelines at that time before evidence of a beneficial effect. Treatment with hydroxychloroquine got remarkable attention primarily due to in vitro data and immunomodulatory capacities, but a meta-analysis demonstrated an association with increased mortality and no clear benefit in hospitalized COVID-19 patients [ 34 , 35 ]. In different clinical trials, treatment with remdesivir showed mixed results and seemed to shorten time to recovery [36] .…”
Section: Discussionmentioning
confidence: 99%
“…1,2 However, empirical evidence supporting this widely held belief is limited, prompting the critique that evidence-based medicine (EBM) overemphasises algorithmic decision rules over physicians' intuition and experience. 3,4 During the COVID-19 pandemic many inadequately tested and unproven therapies have, largely driven by uncontrolled physicians' experience, dominated the practice of medicine 5,6 raising the question if health interventions delivered according to evidenceprotocols could have improved health outcomes. 7 One of the challenges of evaluating evidence-based practices is the lack of a theoretical framework for their evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…During the COVID‐19 pandemic many inadequately tested and unproven therapies have, largely driven by uncontrolled physicians' experience, dominated the practice of medicine 5 , 6 raising the question if health interventions delivered according to evidence‐protocols could have improved health outcomes. 7 …”
Section: Introductionmentioning
confidence: 99%
“…But it must not be forgotten that these bad interventions can cause damage to health [16][17][18]. In addition, the irrational use of auxiliary tests, including computed tomography and X-rays, only increases the anxiety of the patient and the doctor, who is often "forced" to prescribe a treatment directed at the complementary tests instead of clinical condition of patient [19].…”
mentioning
confidence: 99%